A Study of Mutual Coupling between Vertical Grounding Electrodes. Issue 1 (July 2014) - Fujita, Yuta; Ametani, Akihiro; Nakamura, Keisuke; Yamabuki, Koichi
SUMMARY This paper investigates the mutual grounding impedance between vertical grounding electrodes based on field measurements and FDTD simulations. In the case of vertical electrodes, the mutual impedance between the electrodes is almost completely independent of the electrode length, and thus the induced voltage is nearly constant as the electrode length becomes longer. This characteristic is different from that of an overhead conductor, where the electromagnetic‐induced voltage is proportional to the conductor length. The greater the separation distance between the electrodes, the smaller the induced voltage, as in the case of an overhead conductor. The propagation speed increases as the separation increases. It is found that the speed is not necessarily proportional to the inverse of the relative permittivity of the earth.